HyCReWW: A Hybrid Coral Reef Wave and Water level metamodel. (June 2019) - Rueda, Ana; Cagigal, Laura; Pearson, Stuart; Antolínez, Jose A.A.; Storlazzi, Curt; van Dongeren, Ap; Camus, Paula; Mendez, Fernando J.
Abstract: Wave-induced flooding is a major coastal hazard on tropical islands fronted by coral reefs. The variability of shape, size, and physical characteristics of the reefs across the globe make it difficult to obtain a parameterization of wave run-up, which is needed for risk assessments. Therefore, we developed the HyCReWW metamodel to predict wave run-up under a wide range of reef morphometric and offshore forcing characteristics. Due to the complexity and high dimensionality of the problem, we assumed an idealized one-dimensional reef profile, characterized by seven primary parameters. XBeach Non-Hydrostatic was chosen to create the synthetic dataset, and Radial Basis Functions implemented in MATLAB ® were chosen for interpolation. Results demonstrate the applicability of the metamodel to obtain fast and accurate results of wave run-up for a large range of intrinsic reef morphologic and extrinsic hydrodynamic forcing parameters, offering a useful tool for risk management and early warning systems. Highlights: Fast, and accurate estimations of wave-induced water levels on reef-lined coasts. Metamodel based on NH-XBeach hydrodynamic model runs and Radial Basis Functions. Validated mathematically with a k-fold strategy. Validated physically with field observations and lab experiments.